Being "Challenged" and Masking my own Uncertainty: My Parallel Journey with Elementary Prospective Teachers. Issue 2 (4th May 2019) - Simpson, Amber
ABSTRACT: This research utilized self-study methodology to examine my experience as a novice elementary mathematics teacher educator whose foundation was a high school mathematics teacher and graduate training in secondary mathematics education. By analyzing video data of the weekly mathematics methods course, I relived moments in which I masked my uncertainties through engaging the class in discussion, putting up a wall of defense, and through walking away or leaving the discussion unresolved. However, my perspective of these moments was reframed through stimulated recall interviews with two of the prospective elementary teachers enrolled in the course. Our experiences were similar in terms of our tensions and professional growth, our understanding of mathematical concepts, student thinking, and appropriate instructional practices. The insights from this study raised questions regarding a community of learners among teacher educators and prospective teachers.